"Dybest set opfatter jeg mig selv som en fortæller" - Apelt, Helene (Rambam. Tidsskrift for jødisk kultur og forskning, 2012)
"I Consider Myself a Story Teller" Sally Altschuler has written more than 30 children’s books and has recently published his first novel for adults. Helene Apelt (MA in literature) has interviewed Sally Altschuler about his Jewish identity, his relationship to facts and fiction in literature, and not least, about his recent novel based on his own family story that was published in two versions: one for children and one for adults. The interview focuses on the latter. The novel En engel bag øret (An Angel Behind the Ear), from 2011, tells the story of the life of Sally’s ancestors, the Hiswerovitzes. We learn about life in the small village of Antonovka in the Russian Empire in the 19th century and the arrival to Denmark of Grandfather Feivel Altschuler in 1912. The novel incorporates real historical events and is the result of intense research both in Denmark and in Eastern Europe, where, in 2006, Sally and his son travelled back to Antonovka (now located in Belarus). The novel, however, is also full of fun and fantastic characters and stories that challenge the imagination of the reader. For example, the main character, Berel Hiswerovitz, was known to talk with animals. Sally does not aim at a sharp distinction between facts and fiction. ”Reality is created through storytelling,” he says. The author’s own relationship to his Jewish heritage and culture has changed during his life. In his youth, it didn’t affect him that much, but his interest in genealogy and the exploration of the family stories has given his Jewish identity a more prominent role and brought him closer to the Jewish community.